Persepsi pengguna terhadap pelayanan perpustakaan utama Uin Syarif Hidayatullah Jakarta, 2007: Laporan hasil penelitian - Nuryudi Nuryudi (Al Maktabah, 2007)
By using analitical descriptive approach, this survey research was expected to explore the users' perceptions (their impressions, observations, and points of view) towards UIN-main library service's quality. We know that users are effective assessors for library services within a given time. Their various perseptions had been utilized to assess the states of main elements of library services. As can be seeen from the gatherred datum, user perceptions which stated good on the overall library services are higher than that of which saying worse. Nevertheless, their admission of dissatisfaction in recieving the services even higher than those expressing and feelling satisfied. Although on the overall library servcices, most of the respondens saying good but only small proportion of them admitted themselves satisfied with the library service provision in the mid 2007. In short the majority of respondents stated that they were dissatisfied with the UIN main library services in the time. Key Words: Persepsi user, pelayanan perpustakaan, kwalitas pelayanan, sumber daya pelayanan, sikap mental pelayanan, kemudahan pelayanan, dan kepuasan layanan